Simulasi Perhitungan Awal Waktu Salat Berdasarkan NOAA Solar Calculator Menggunakan Spreadsheet - Taufikurrahman, Arief (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
The development of science encourages the presence of new methods in determining the beginning of the prayer time. One of them is the reckoning method which utilizes astronomical data to determine the beginning of the prayer time. This study aims to simulate the initial calculation of prayer times based on ephemeris data from the National Oceanic and Atmospheric Administration (NOAA) using a spreadsheet. The prayer times resulting from the simulation are not much different from the prayer times published on the BIMAS Kementerian Agama Republik Indonesia website